Parafrase Dan Sintesis Dalam Mengelola Sumber Ilmiah - Siti Annisa Nurfadilah; Wardah Azizah Azizah; Rika Sadiyah (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2026)
The publication of scientific papers demands high standards of originality free from plagiarism, thereby requiring researchers to possess strong competence in managing reference sources. This study aims to comprehensively examine the roles, concepts, and implementation of paraphrasing and synthesis techniques in academic writing. Utilizing a descriptive-analytical approach, it argues that paraphrasing functions as an instrument for restructuring a single text using personal language to avoid plagiarism without altering the original meaning. Meanwhile, synthesis plays a role as a transformative cognitive process that combines multiple sources through matrix creation and thematic categorization to build new, holistic arguments and identify research gaps. The results of the study show that the proper integration of paraphrasing and synthesis is not only effective in reducing the similarity index on Turnitin software but also reflects the depth of the researcher's understanding of the literature. In conclusion, mastering these two skills is highly crucial for enhancing the quality of writing nuance, maintaining academic integrity, and presenting a credible map of scientific information for the advancement of science. Keywords: Paraphrasing, Plagiarism, Synthesis.